DMD-Null mice exhibit severe muscle weakness, impaired regeneration, and deficient satellite cell function - Harry Wilton-Clark; Md Nur Ahad Shah; Jamie Leckie; Sebastian Hernandez Rodriguez; Ammar Al-Aghbari; Pavel Zhabyeyev; Rika Maruyama; Yoshitsugu Aoki; Gavin Y. Oudit; Toshifumi Yokota (Proceedings of the National Academy of Sciences, 2026)
Duchenne muscular dystrophy (DMD) is a debilitating and fatal X-linked disease affecting 1/5,000 males worldwide that currently has no cure [D. Duan, N. Goemans, S. Takeda, E. Mercuri, A. Aartsma-Rus, Nat. Rev. Dis. Primers 7 , 1–19 (2021), 10.1038/s41572-021-00248-3]. Vast amounts of research have been conducted on DMD, and one of the most common animal models for DMD studies is the mouse muscular dystrophy ( mdx ) model [J. W. McGreevy, C. H. Hakim, M. A. McIntosh, D. Duan, DMM Dis. Model. Mech. 8 , 195–213 (2015), 10.1242/DMM.018424/-/DC1]. Unfortunately, despite its shared genetic etiology, the mdx mouse shows a relatively mild dystrophic phenotype compared to affected humans, limiting its overall utility as a research model (G. Donen, N. Milad, P. Bernatchez, J. Neuromuscul. Dis. 10 , 1003 (2023), 10.3233/JND-230126]. Notably, mdx mice have a mutation preventing the production of full-length dystrophin but are still able to produce numerous short isoforms of dystrophin. Here, we provide a comprehensive functional characterization of DMD-Null mice, which lack all dystrophin isoforms. Our studies demonstrate that DMD-Null mice show a more severe skeletal muscle phenotype than mdx mice, characterized by profound weakness, decreased exercise tolerance, and impaired muscle regeneration, while utrophin upregulation was similarly observed in DMD-Null and mdx mice. We identify a marked deficit in satellite cell proliferation and myogenic differentiation, accompanied by downregulation of regenerative gene programs. These findings suggest potential contributions of short dystrophin isoforms to muscle stem cell function, and establish DMD-Null mice as a unique model for investigating the pathogenesis of DMD and testing therapeutic interventions targeting satellite cell health and regeneration.